PERUSAHAAN TIDAK PATUH SYARIAH: ANALISIS FAKTOR PENYEBAB DIKELUARKANNYA PT BUKALAPAK.COM TBK DARI DAFTAR EFEK SYARIAH - nusrida, helda; -, rozalinda; wira, ahmad (Universitas Islam Negeri Imam Bonjol Padang, 2023)
The purpose of this research is to find out the causes of a company being excluded from the list of sharia securities. The research method in this research is descriptive qualitative research with the research object PT.Bukalapak.com Tbk, the data source in this research is a secondary data source with data collection in the form of documentation and literature studies and phenomenological analysis techniques. The results of the study show that the company's activities carried out by PT.Bukalapak.com Tbk conflict with sharia principles. In terms of financial ratio, PT. Bukalapak.com Tbk has usury-based debt which exceeds the total assets owned by the company. Corporate cooperation activities that violate sharia principles by supporting conventional banking activities by buying shares of ALLO Bank. PT Bukalapak.com Tbk is still trading alcoholic drinks and sex toys. PT.Bukalapak.com Tbk does not meet the criteria and the publication of the list of sharia securities is by PJOK No.35/POJK.04/2017.